Reproducible Temperament Profiles in Adolescents With Attention-Deficit/Hyperactivity Disorder Prospectively Predict Clinical Outcomes - Michael B. Kozlowski; Jaden A. Sangoi; Hannah E. Morton; Elizabeth K. Nousen; Jessica M. Tipsord; McKenzie T. Figuracion; Sarah Pieper; Erica D. Musser; Joel T. Nigg; Sarah L. Karalunas (Clinical Psychological Science, 2026)
Currently, the field faces controversy about how to integrate novel, trait-based dimensions into existing psychological diagnostic frameworks. The problem is salient for attention-deficit/hyperactivity disorder (ADHD), which encompasses a partially coherent neurodevelopmental syndrome that is nonetheless heterogeneous with respect to mechanism and outcomes. Here, we suggest that temperament profiles, related to trait-based variation in emotional response and regulation, provide a viable way to link the complexity of within-group trait variation to differences in clinical outcomes. Across two large, independent samples of adolescents with ADHD (Oregon ADHD–1000, Adolescent Brain Cognitive Development Study), we identified largely reproducible temperament profiles: a high-approach-motivation profile (“surgent”) and a high-negative-emotion profile (“irritable”). In both samples, the irritable profile prospectively predicted worsening clinical outcomes over multiple years of longitudinal follow-up. Temperament-profiling approaches can contribute to improved risk/resilience prediction among individuals with ADHD and help bridge dimensional models of psychopathology with developmental process and clinical decision-making.